FEATURES OF THE DEVELOPMENT OF THE OIL AND PIPE INDUSTRY AS OBJECT OF STUDY TO IDENTIFY STRATEGIC GUIDELINES FOR THEIR INTERACTION - A. Borozdin (Вестник университета)
The research topics in the article are the oil industry and the industry for the production of tubes for pipelines, two strategically important industries, to provide energy for the Russian Federation and the international export. The author focuses his attention on the identification of scientific and economic, industrial and technical interaction problems of these two industries. The main strategic goal of the oil industry and the industry for the production of tubes for pipelines must be the economic supply security of the Russian Federation to ensure the effective promotion of the socio economic development of the countr.